"Pharmtech & Ingredients –2024" - article Editorial (Разработка и регистрация лекарственных средств)
From November 19 to 22, 2024, the 26th International Exhibition of Equipment, Raw Materials and Technologies for Pharmaceutical Production "Pharmtech & Ingredients – 2024" was held in Moscow.